2009
DOI: 10.4310/mrl.2009.v16.n6.a13
|View full text |Cite
|
Sign up to set email alerts
|

A proof of Lens Rigidity in the category of Analytic Metrics

Abstract: Abstract. Consider a compact Riemannian manifold with boundary. If all maximally extended geodesics intersect the boundary at both ends, then to each geodesic γ(t) we can form the triple (γ(0),γ(T ), T ), consisting of the initial and final vectors of the segment as well as the length between them. The collection of all such triples comprises the lens data. In this paper, it is shown that in the category of analytic Riemannian manifolds, the lens data uniquely determine the metric up to isometry. There are no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…We replace nextZ( (z − ), z − ) byZ ˜ (z − ),z − =z + modulo errors controlled by (49), (50), so that we can get z + − z − on the left; and use the fact that the latter satisfies (49). This would allow us to conclude that the integral is "small" in U in .…”
Section: ∂Mmentioning
confidence: 99%
“…We replace nextZ( (z − ), z − ) byZ ˜ (z − ),z − =z + modulo errors controlled by (49), (50), so that we can get z + − z − on the left; and use the fact that the latter satisfies (49). This would allow us to conclude that the integral is "small" in U in .…”
Section: ∂Mmentioning
confidence: 99%
“…The second follows from the fact that the two systems share the same length data. See [24] for details.…”
Section: Proposition 2φ Is a Well-defined Function On Sm 1 With Valuementioning
confidence: 98%
“…This has been done in the absence of magnetic fields in [24]. The proof carries over in the presence of magnetic fields with only changes in notation.…”
Section: Theorem 4: Construction Of the Magnetic Equivalencementioning
confidence: 99%
See 1 more Smart Citation
“…Stefanov and Uhlmann [38] proved uniqueness up to diffeomorphisms fixing the boundary for metrics sufficiently close to a generic regular metrics. Vargo [43] showed that a class of analytic metrics are lens rigid. On the other hand, some interesting special cases of the lens rigidity problem with trapped geodesics are studied in [11,13].…”
mentioning
confidence: 99%